Antimalarial and antioxidant activities of novel artesunate-ellagic acid hybrid compound in vitro and in vivo - Ishola, Ahmed A.; Adebayo, Joseph O.; Ceravolo, Isabela P.; Tijjani, Habibu; Bento, Edson S.; Goulart, Henrique F.; Crispim, Alessandre C.; Balogun, Elizabeth A.; Santana, Antonio E. G.; Krettli, Antoniana U. (Frontiers in Pharmacology, 2024)
Introduction: Emergence of drug resistant strains of Plasmodium species has necessitated the search for novel antimalarials with unique mechanisms of action. Synthesis of hybrid compounds has been one approach to tackling this challenge. In this study, the synthesis of artesunate-ellagic acid hybrid compound (EA31) from ellagic acid and artesunate and its evaluation for antimalarial and antioxidant activities using in vitro and in vivo models were carried out.Method: EA31 was synthesized from artesunate and ellagic acid. The activities of the hybrid compound against Plasmodium falciparum W2 and P. berghei NK65 were evaluated, and its antioxidant activities were also determined.Results: The results revealed that EA31 was more active against P. falciparum W2 (chloroquine resistant) clone and less cytotoxic to buffalo green monkey (BGM) kidney cell line compared to artesunate. EA31 was also active against P. berghei NK65 in vivo. The results revealed inhibition of β-hematin formation as one of the mechanisms of action of EA31. EA31 also exhibited antioxidant activities.The results revealed that EA31 may exert dual action of killing malaria parasite and mopping the reactive oxygen species that mediate the secondary complications of malaria.